DIMENSI HARGA SAHAM DILIHAT DARI RASIO KEUANGAN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERFADTAR DI BEI - Githa Miranda Indika Putri; Masitoh , Endang; Nikmatul Fajri , Rosa (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
The purpose of this study is to examine and analyze the effect of financial ratios on stock prices. The population in this study are food and beverage companies listed on the IDX. The number of samples in this study were 43 samples. Financial ratios are proxied by Current Ratio, Debt to Equity Ratio, Return On Equity and Earning Per Share. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that simultaneously CR, DER, ROE and EPS have a significant effect on stock prices. Partially CR and DER have no significant effect on stock prices. While ROE and EPS have a significant effect on stock prices. The coefficient of determination (R2) test results of 0.603, 60.3% of the dependent variable can be explained by the variables CR, DER, ROE and EPS, while the rest are explained by other variables not used in this study. Keywords: CR, DER, ROE, EPS, Stock Prices